Parliamentary representation and political accountability: a case study of ghana’s fourth republic. - Dankwa, Charles (KNUST, 2025)
This Thesis Is Submitted In Partial Fulfillment Of The Requirements For The Award Of Degree In Master of Philosophy in Political Science